Surface Modification Technologies for Space and Planetary Applications - Якоб Клеймен (Mechanics and Advanced Technologies)
This paper presents an overview of processes developed in our company for applications in various space and planetary environments. A number of materials including polymers, paints and other organic-based materials undergo dramatic changes and irreversible degradation of physical and functional characteristics when exposed to space or planetary environments, like in LEO, GEO or on Moon, or Mars. Protective schemes including protective coatings, mechanical metal foil wrapping or cladding, specially synthesized bulk materials, etc. are used to reduce the effects of space environment on materials and their properties. However, the protection of polymers, paints and other organic-based materials in space still remains a major challenge, especially for future long duration exploration missions to other planets or permanent space stations or for an ever-growing array of nano-, micro- and macro-satellites in VLEO, LEO and GEO orbits. Surface modification processes and advanced coatings are used increasingly to protect existing or provide new properties to polymers, paints and other organic-based materials. A number of surface modification solutions that include treatment of the surfaces by chemical or physical processes and that differ from the traditional protective coating approaches were developed by ITL in the last 30 years that change the surface properties of treated materials, protecting them from the hazards of low Earth orbit (LEO) and Geostationary orbit (GEO) environments or providing dust mitigation properties when used in Lunar environment. Examples of their testing, characterization and applications are provided. In addition, a surface treatment process for mitigation of lunar dust effects in lunar environment was developed and will be discussed.